Human immunodeficiency virus status disclosure among people living with human immunodeficiency virus receiving care in Enugu, Nigeria: A mixed method study - Ifeoma Maureen Obionu; Chinyere Cecilia Okeke; Ikechukwu Eke-Okoro; Emmanuel Nwabueze Aguwa; Chika Nwanma Onwasigwe (Wolters Kluwer Medknow Publications, 2021)
Background: Disclosure of human immunodeficiency virus (HIV) status has potential benefits for both the individual and society. Objectives: This study aimed to determine the disclosure rate and its associated factors in people living with HIV receiving care in Enugu, Nigeria. Methods: A cross-sectional study using mixed methods was carried out in 5 comprehensive treatment facilities in Enugu, Nigeria during March to August 2019. 300 participants for the quantitative aspect were selected using a simple random sampling method and 30 participants for the qualitative aspect were selected purposively. Interviewer administered questionnaire and focus group discussion were applied for data collection. The quantitative data was analyzed using Epi info version 7; Chi-square test and multivariable logistic regression were applied and a level of statistical significance was set at P < 0.05. The qualitative data were analyzed using thematic analysis. Results: Among 300 participants, 241 (80.3%) had voluntarily disclosed their status to someone within their social network. 228 respondents had sexual partners and 122 (52.4%) had disclosed to their sexual partners. Twenty-five (11.0%) disclosed to their partners on the day of diagnosis. Predictors of disclosure were being female, having a formal education and being 35 years or more. Conclusion: This study revealed high voluntary disclosure rate to someone within the social network, but lower and delayed disclosure rate to sexual partners.